Analisis Kepuasan Pengguna Terhadap Sistem E–Raport Menggunakan Metode EUCS dan Model Delone and McLean - Hengky Hengky; Satrianansyah Satrianansyah (JURIKOM (Jurnal Riset Komputer), 2022)
The problem discussed in this study is the E-Raport System used by SMK Muhammadiyah Lubuklinggau City, since the beginning of 2017 the use has never been evaluated, measuring the performance of the satisfaction of using the application. So that it is not yet known how effectively the application can help its users, so from this problem researchers Measure User Satisfaction from the success of the E - Report System in SMK Muhammadiyah Lubuklinggau City using the EUCS method and the McLean Model. This study is about analyzing the level of satisfaction of E-Raport users at SMK Muhammadiyah Lubuklinggau. This study aims to determine the application of the system that has been used and to determine the level of satisfaction of users of the E-Raport system at SMK Muhammadiyah Lubuklinggau. This study uses 2 methods of End User Computing Satisfaction (EUCS). ) and the Delone and McLean models. The EUCS method emphasizes user satisfaction, by analyzing the system based on content, accuracy, appearance, convenience and timeliness, while the Delone and McLean Model method analyzes system user satisfaction based on System Quality, Information Quality, Service Quality. This type of research is a descriptive type using research instruments in the form of a questionnaire. With 40 respondents, the results are valid and mutually influence user satisfaction. (This study uses a measuring instrument in the form of a questionnaire distributed to 40 respondents who are teachers of SMK Muhammadiyah Lubuklinggau). From the results of the analysis that has been carried out, the following results are obtained for the validity test using the EUCS method that is valid to use, and for the validity test the Delone and Mclean model method is valid to use, for the reliability test of the two reliable methods to be used, and for the results of the T test and test F stated that the two methods mutually influence user satisfaction